Computationally predicted energies and properties of defects in GaN - John L. Lyons (Nature Portfolio, 2017)
Abstract Recent developments in theoretical techniques have significantly improved the predictive power of density-functional-based calculations. In this review, we discuss how such advancements have enabled improved understanding of native point defects in GaN. We review the methodologies for the calculation of point defects, and discuss how techniques for overcoming the band-gap problem of density functional theory affect native defect calculations. In particular, we examine to what extent calculations performed with semilocal functionals (such as the generalized gradient approximation), combined with correction schemes, can produce accurate results. The properties of vacancy, interstitial, and antisite defects in GaN are described, as well as their interaction with common impurities. We also connect the first-principles results to experimental observations, and discuss how native defects and their complexes impact the performance of nitride devices. Overall, we find that lower-cost functionals, such as the generalized gradient approximation, combined with band-edge correction schemes can produce results that are qualitatively correct. However, important physics may be missed in some important cases, particularly for optical transitions and when carrier localization occurs.